Temporal trends in mortality from diabetes mellitus in Colombia by sex: An Age Period Cohort Analysis (2025)
Background: Mortality from diabetes mellitus (DM) has shown significant variation over time in Colombia. However, the factors influencing this trend and potential sex differences have not yet been fully explored. Objective: To estimate the contributions of age, period, and birth cohort effects on DM mortality trends in Colombia by sex from 1983 to 2022. Methods: Analytical observational study, using pooled cross-sectional data from mortality records and population projections from the National Statistics Department. The count of DM deaths for each age, period, and cohort group was organized into five-year intervals. A multiple quasi-Poisson model was applied using the intrinsic estimator method with collapsing intention. Mortality rate ratios (MRR) for each age, period, and cohort group by sex were reported in comparison to the overall average rate, along with a 95% confidence interval (CI). Results: During the study period, 234,117 DM-related deaths were recorded, with a mortality rate of 12.74 and 16.34 deaths per 100,000 persons for men and women, respectively. For both sexes, as age increased, DM mortality also rose, with the 85+ age group presenting the highest MRR (Men: 17.84; 95% CI: 16.07-19.81 and Women: 18.49; 95% CI: 16.75-20.40). Regarding the cohort effect, higher MRR was observed in older birth cohorts. For the 1898-1902 cohort, the MRR in men was 1.51 (95% CI: 1.34-1.72) and in women 1.60 (95% CI: 1.42-1.81), compared to the youngest cohort (2018-2022), where the MRR for men was 0.10 (95% CI: 0.04-0.21) and for women 0.12 (95% CI: 0.05-0.34). Finally, regarding the period effect, the MRR for the years 2018-2022 was significantly higher in men compared to women, with an MRR of 1.45 (95% CI: 1.37-1.52) and 1.26 (95% CI: 1.20-1.33), respectively. Conclusion: Public health actions aimed at reducing DM mortality in Colombia should prioritize early detection, promotion of healthy aging, access to medications, continuous monitoring, prevention, effective management of complications and comorbidities, and raising awareness about health care in all generations.